TERRITÓRIO DA PROSTITUIÇÃO E INSTITUIÇÃO DO SER TRAVESTI EM PONTA GROSSA – PR - Ornat, Marcio Jose (2008)
The objective of this work is to understand the co-relation between the territory of travesti prostitution and the institution of the subject travesti in the city of Ponta Grossa, Parana. The linearity between sex, gender, sexual practices and sexual desire is a common feature of contemporary western society that seeks at all costs to keep explanations of the order based on the heterosexual nature of the bodies and behaviour. From this perspective the subjects that do not correspond to the standards established are considered deviant, patients and many qualitative created to classify the society and maintain their alleged natural order. The focus group elected to this search is precisely that which defies simplistic explanations and complexifica the established order, the travesti. We use this term to appoint people that they identified and that, in their majority, were involved with the activity of prostitution. The spatiality developed by travestis are elements of fundamental importance in the existence of the group, even if marginal. The space determines the positions of subjects, composed relations of forces, and guides the choices and their understanding of the reality. After the analysis of all interviews conducted with the focus group of travestis, found a set of 906 evocations for relations established in the family, relations of conjugality, and the relationship between this group and travestis with residents and police. The spatiality that comprise the memoirs travestis simultaneously create the bonds of affection the group of belonging and differentiation among other groups. It’s constitute of experience travesti and identity travestis, heteronormativity related to reproduction, as well as their transgression. The main spatiality mentioned in the speeches of the travestis were related to the house, the urban space, and the territory. The experiences which are experienced by travestis, related to home and the urban space, are shared in the group by promoting processes of identification, a process that flow for space that becomes territory. It is the experience of the area, established by rules and behaviors oriented to the bodies, which produce the identities travestis, achieving locate these people to other social groups. However, the positions of subjects are mobile in central and margin, as the territory of travestis prostitution is relational, involving configurations of power between the subjects that shape relations. The territory consists of multiple dimensions, as the transvestite in each of them is in center and margin of power relations. This is possible various location of travestis that can subvert the order of forces between me and other, because they are both separate and connected. The territory is a place to get gains from the marketing of sexual practices, but also an important element in the constitution of being travestis, as a place of learning to be travestis. Territory that is made and constituent, as well as body, sex, gender, desire and life.